Anxiety and Drinking: Are Personal Beliefs Regarding Control and Unpredictability Relevant?. Issue 8 (17th November 2018) - Thomson Ross, Lisa; Hasty, Jazmine
Abstract: Anxiety and drinking problems are fairly common, and it is important to know what factors affect these issues. Previous studies document that control beliefs are associated with anxiety and drinking. Unpredictability beliefs correlate with anxiety, yet whether they relate to drinking is unknown. The present study explored these relationships in a sample of adults ( N = 150; 40.0% female; M = 34.4 years old) and in a sample of college students ( N = 182; 74.7% female; M = 18.9 years old). Among adults, unpredictability beliefs correlated with anxiety and control beliefs, but not drinking. Similarly, control beliefs correlated with anxiety but not drinking. Furthermore, anxiety and drinking were uncorrelated. Among undergraduates, unpredictability and control beliefs predicted anxiety, whereas unpredictability (pertaining to the self and others) and internality predicted frequency of drinking. Personal unpredictability beliefs emerged as having the strongest association with anxiety across both samples. Future research and treatment should take into account unpredictability beliefs when addressing anxiety problems.